An integrated economic model of multiple types and uses of water. Issue 5 (16th May 2014) - Luckmann, Jonas; Grethe, Harald; McDonald, Scott; Orlov, Anton; Siddig, Khalid
Abstract Water scarcity is an increasing problem in many parts of the world and the management of water has become an important issue on the political economy agenda in many countries. As water is used in most economic activities and the allocation of water is often a complex problem involving different economic agents and sectors, Computable General Equilibrium (CGE) models have been proven useful to analyze water allocation problems, although their adaptation to include water is still relatively undeveloped. This paper provides a description of an integrated water‐focused CGE model (STAGE_W) that includes multiple types and uses of water, and for the first time, the reclamation of wastewater as well as the provision of brackish groundwater as separate, independent activities with specific cost structures. The insights provided by the model are illustrated with an application to the Israeli water sector assuming that freshwater resources available to the economy are cut by 50%. We analyze how the Israeli economy copes with this shock if it reduces potable water supply compared with further investments in the desalination sector. The results demonstrate that the effects on the economy are slightly negative under both scenarios. Counter intuitively, the provision of additional potable water to the economy through desalination does not substantively reduce the negative outcomes. This is mainly due to the high costs of desalination, which are currently subsidized, with the distribution of the negative welfare effect over household groups dependent on how these subsidies are financed.